ENFORCEMENT LAW BY POLICE FORESTRY AS INVESTIGATOR EMPLOYEE COUNTRY CIVIL RESPONSIBILITY IN COMBATING THE CRIMINAL ACTS OF ILLEGAL LOGGING IN CITY PALANGKA RAYA - Aini Happy Patricia; Yacob Ferdinan Martono; Rizki Setyobowo Sangalang; Achmad Adi Surya Guntur Silam (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Indonesia, US a country endowed with abundant forest resources, faces various forestry-related issues, one of which is illegal logging. Central Kalimantan, particularly the city of Palangka Raya, is among the regions affected by illegal logging activities, which not only cause environmental degradation but also result in economic and social losses. This study aims to analyze lawenforcement efforts carried out by Police Forestry (Forest Rangers) US Civil Servant Investigators (PPNS) in combating illegal logging in Palangka Raya, as well as to identify the obstacles encountered in its implementation. This research employs a juridical-empirical method with a descriptive qualitative approach. Data were obtained through interviews with relevant authorities and literature studies, particularly referring to Law Number 41 of 1999 and Law Number 18 of 2013. The results indicate that lawenforcement efforts are carried out through both preventive and repressive approaches. Preventive measures include publicawareness programs, reforestation, establishment of guard posts, and improvement of human resource capacity. Meanwhile, repressive efforts involve patrol activities, law enforcement operations, and legal actions against perpetrators of illegal logging. Thedata show a decline in the number of cases from 2023 to 2025, indicating an improvement in the effectiveness of law enforcement.